Annual variation of in situ sedimentation of planktonic Ciliophora cysts in a temperate bay - Yu, Ying; Zhang, Wuchang; Lin, Zhenxian (Frontiers in Marine Science, 2023)
Marine planktonic Ciliophora serve as a key component of the plankton food web. The formation of cysts is of common occurrence among planktonic Ciliophora, and encystment plays an important role in the persistence and diffusion of population. However, studies on the seasonal pattern of encystment of planktonic Ciliophora in natural environments were limited. Here, we investigated the sedimentation of Ciliophora cysts, and explored the seasonal differences of encystment between aloricate Oligotrichea and Tintinnina in Bohai Bay. Ciliophora cysts were collected monthly with a sediment trap from July 2019 to June 2020 at a fixed station, and identified according to the morphological characteristics of cysts by fluorescence microscopy. Ten types of aloricate Oligotrichea cysts were identified and only three species of Tintinnina cysts were recognized, namely, Favella sp., Helicostomella longa and Tintinnopsis sp. There were obvious seasonal differences of encystment between aloricate Oligotrichea and Tintinnina. Encystment of Tintinnina mainly occurred in summer, while encystment of aloricate Oligotrichea was found at all seasons and the seasonal patterns varied among species. The production rate of several types of cysts showed significant positive correlations with water temperature and Chlorophyll a concentration, and a significant negative correlation with salinity. Our study exhibited that the seasonal pattern of encystment of Ciliophora varied greatly from species to species, and assessing seasonal patterns of encystment will aid our ability to understand the mechanism of vegetative population dynamics.